ANALISIS TINGKAT RISIKO PENYALURAN KREDIT USAHA RAKYAT (KUR) DALAM MENINGKATKAN KINERJA KEUANGAN PADA PT. BANK SULSELBAR CABANG GOWA - Rizal, Samsul; Nadwah, Nadwah (Jurnal Ekonomi Balance, 2016)
This study uses Descriptive analysis and Credit Risk analysis using quantitative methods. Used to determine the level of risk of Kedit KUR at PT. SulselBar Bank, Gowa Branch. Data in the form of credit collectability reports, and data obtained in writing in the form of a general description of the company, namely data collection through direct interviews in the credit section with the problems examined at PT. Bank of Sulselbar Branch of Gowa.The results of the study concluded that non-performing loans (NPL) at PT. Bank Sulselbar, Gowa branch is classified as medium in accordance with the provisions of Bank Indonesia (BI). In the analysis of financial performance using ratio analysis consisting of liquidity ratios, solvency ratios and profitability ratios. The results of the study concluded that those who experienced an increase were based on the percentage of the solvency and profitability ratios.